(untitled) (mathematica didactica, 2006)
Motivational variables are considered as meaningful individual dispositions for learning processes. On the basis of empirical findings concerning motivation, interest and self concepts in mathematics of grade 8 students, we focus on interactions between different motivation-related variables. Results from a cluster-analysis of the quantitative data gainedin a field study indicate that different motivational profiles might play particular roles for the development of motivational variables and proof competence, which seem not to be independent from specific learning environments.